Effect of age, time spent in prison and level of education on the perceived health and quality of life of elderly prisoners. Issue 2 (10th June 2019) - Combalbert, Nicolas; Pennequin, Valérie; Ferrand, Claude; Keita, Moussa; Geffray, Brigitte
Abstract : Purpose: The purpose of this paper is to assess the level of perceived health and quality of life of elderly prisoners in France, and to see whether there is a link between aging, time spent in prison and level of education and scores for perceived health and quality of life. Design/methodology/approach: The authors' recruited 138 male prisoners aged 50 and over in seven French prisons. The research protocol comprised a semi-structured interview and two scales. Findings: The results revealed low levels of perceived health and quality of life among the elderly inmates. They also showed that age was not statistically associated with most of the dimensions of perceived health on the Nottingham Health Profile (NHP), with the exception of poor mobility. By contrast, age was statistically associated with most of the dimensions of quality of life on the WHOQOL-Bref. Time spent in prison was only associated negatively with the "sleep" dimension of the NHP. Emotional reactions were perceived most positively by the inmates with the highest level of education. Practical implications: It seems particularly important to assess the perceived health and quality of life of elderly prisoners in order to ensure their appropriate treatment and management. Originality/value: Very few studies have examined the perceived health and quality of life of prisoners, even though this population is particularly vulnerable in terms of physical and mental health.